On the European Union: Turkey customs union - Sübidey Togan (Center for Social and Economic Research (CASE), 2011)
The purpose of the paper is to study the European Union - Turkey customs union (CU) of 1995 covering trade in industrial goods. The customs union decision of 1995 extending to rules and disciplines on various regulatory border and behind-the-border policies covers in particular customs reform, technical barriers to trade, competition policy, intellectual property rights, and administrative procedures. The paper after assessing in each case the status quo at the time of the entry of the CU into force evaluates the commitments undertaken under the CU, and assesses the degree of implementation of the CU requirements as well as the administrative costs of implementation of the CU. Finally, the paper shows how the CU has successfully moved the Turkish economy from a government-controlled regime to a market based one.
Keywords: F15; 330; Economic Integration; Customs Union; Wirtschaftsintegration; Zollunion; Türkei; EU-Staaten